2014
DOI: 10.1099/mic.0.075465-0
|View full text |Cite
|
Sign up to set email alerts
|

A new tubRZ operon involved in the maintenance of the Bacillus sphaericus mosquitocidal plasmid pBsph

Abstract: A new tubRZ operon involved in the maintenance of the Bacillus sphaericus mosquitocidal plasmid pBsph pBsph is a mosquitocidal plasmid first identified from Bacillus sphaericus, encoding binary toxins (Bin toxins) that are highly toxic to mosquito larvae. This plasmid plays an important role in the maintenance and evolution of the bin genes in B. sphaericus. However, little is known about its replication and partitioning. Here, we identified a 2.4 kb minimal replicon of pBsph plasmid that contained an operon e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 39 publications
(58 reference statements)
5
31
0
Order By: Relevance
“…The TubX protein with a six-histidine (His 6 ) tag at the C terminus was purified from E. coli, and the TubR-Bs protein was prepared as described previously (21). The pET28b-tubX expression plasmid was constructed by PCR amplification of the tubX sequence from the B. sphaericus C3-41 genome using primer pair 187-F/187-R.…”
Section: Quantitative Real-time Pcr (Qpcr)mentioning
confidence: 99%
See 3 more Smart Citations
“…The TubX protein with a six-histidine (His 6 ) tag at the C terminus was purified from E. coli, and the TubR-Bs protein was prepared as described previously (21). The pET28b-tubX expression plasmid was constructed by PCR amplification of the tubX sequence from the B. sphaericus C3-41 genome using primer pair 187-F/187-R.…”
Section: Quantitative Real-time Pcr (Qpcr)mentioning
confidence: 99%
“…The relative RNA abundance of each gene compared to that of rpoB was calculated using the 2 Ϫ⌬⌬CT comparative method (25,26), and the results were obtained from the analyses of at least four independent RNA samples. The copy number of the pBsph plasmid in B. sphaericus was measured by qPCR by the method described previously, using the chromosome-specific reference gene adk (21).…”
Section: Quantitative Real-time Pcr (Qpcr)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, TubZRC alone maintains synthetic plasmids only under artificial selective pressure (7,11), and replication of pBtoxis occurs without the dnaAbox but not without TubZRC, prompting others to propose a role for the TubZRC system in plasmid replication (12). In vitro, TubZ assembles into two-and four-stranded polymers (13)(14)(15)(16), and structural studies suggested that the centromeric TubRC complex forms a ring-like structure (17), interacting with the long C-terminal TubZ extensions (18).…”
mentioning
confidence: 99%